Histopathological and electron microscopic study for different grades of inferior oblique muscle overaction - Hamdi MM (Dove Medical Press, 2013)
Momen M Hamdi,1 Golzamine R El-Hawary,1 Nadia G El-Hefnawy,2 Manal I Salman21Ophthalmology Department, 2Pathology Department, Faculty of Medicine, Ain Shams University, Cairo, EgyptPurpose: To correlate between the clinical degree of inferior oblique muscle (IO) overaction and the histopathological changes of the muscle.Settings: Departments of Ophthalmology and Pathology, Faculty of Medicine, Ain Shams University, Cairo, Egypt.Patients and methods: Biopsies from 12 IO muscles were taken during strabismus surgery for cases of IO muscle overaction. One biopsy from a normal IO was taken as a control. All samples were examined under light microscopy and transmission electron microscopy.Results: In light microscopy, all cases showed histopathological changes, in the form of degenerated and regenerating muscle fibers, increased fibrofatty infiltration, and mild variability of muscle fiber size. Hypertrophied nerve bundles also appeared in biopsies from patients with grade II and grade III IO overaction. Endomysial and perimysial fibrosis, mononuclear inflammatory infiltrates, and focal fatty infiltration were seen in biopsies from cases of grade III IO overaction. In electron microscopy, ultrastructural examination revealed an increased number of mitochondria associated with some degree of mitochondrial pleomorphism. Hypercontracted fibers, vacuoles, and fat droplets were also noticed.Conclusion: IO overaction is always accompanied by histopathological changes that differ in severity according to the clinical grading of the overaction. Changes in nerve fibers can also occur in severe cases.Keywords: inferior oblique, electron microscope, overaction, histopathological, muscle fibers